Vagus Nerve Stimulation Promotes Epithelial Proliferation and Controls Colon Monocyte Infiltration During DSS-Induced Colitis - Meroni, Elisa; Stakenborg, Nathalie; Gomez-Pinilla, Pedro J.; Stakenborg, Michelle; Aguilera-Lizarraga, Javier; Florens, Morgane; Delfini, Marcello; de Simone, Veronica; De Hertogh, Gert; Goverse, Gera; Matteoli, Gianluca; Boeckxstaens, Guy E. (Frontiers in Medicine, 2021)
Background: We previously showed increased susceptibility to dextran sulfate sodium (DSS)-induced colitis in vagotomized mice. Here, we evaluated whether vagus nerve stimulation (VNS) is able to reduce the severity of DSS colitis and aimed to unravel the mechanism involved. Methods: Colitis was induced in wild type mice by 2.5% DSS administration in drinking water for 5 days. VNS (5 Hz, 1 ms, 1 mA) was applied 1 day prior to and after 4 days of DSS administration to evaluate changes in epithelial integrity and inflammatory response, respectively. Epithelial integrity was assessed using TUNEL and Ki67 staining. Monocytes, immature and mature macrophages were sorted from colonic samples and gene expression levels of pro-inflammatory cytokines were studied. Results: VNS applied prior to DSS administration (i.e. prophylactic VNS) reduced disease activity index (VNS 0.8 ± 0.6 vs sham 2.8 ± 0.7, p< 0.001, n=5) and tended to improve histology score. Prophylactic VNS significantly increased epithelial cell proliferation and diminished apoptosis compared to sham stimulation. VNS applied at day 4 during DSS administration (i.e. therapeutic VNS) decreased the influx of monocytes, monocyte-derived macrophages and neutrophils, and significantly reduced pro-inflammatory cytokine expression (i.e. Tnfα, Cxcl1 and Il6) in immature macrophages compared to sham stimulation. Conclusions: A single period of VNS applied prior to DSS exposure reduced DSS-induced colitis by an improvement in epithelial integrity. On the other hand, VNS applied during the inflammatory phase of DSS colitis reduced cytokine expression in immature macrophages. Our data further underscores the potential of VNS as novel therapeutic approach for inflammatory bowel diseases.